Perbedaan manifestasi klinis dan laboratorium kolestasis intrahepatal dengan ekstrahepatal pada bayi di RSUP Sanglah Denpasar periode Januari 2015 - Desember 2018 - Pande Putu Agung Willa Kesawa Putra; IGN Sanjaya Putra; I Nyoman Budi Hartawan (Intisari Sains Medis, 2019)
Introduction: Physiological jaundice found in infants and most symptoms are often mild. In conjugated jaundice defects in intra-hepatic production, transmembran transport from bile, i.e. cholestasis intrahepatic, or extra-hepatic obstruction/cholestasis occur, resulting in bile barriers. This study was conducted to look at the differences in the clinical and laboratory manifestations of IH and EH cholestasis in infants.Method: A descriptive retrospective study was performed on 102 infants with cholestasis who came to Sanglah Hospital Denpasar, during the period of January 2015 – December 2018. Data analysis was performed with pearson Chi-square test and independent t-test.Result: Subjects consisted of 60 infants boys and 42 infant girls, intrahepatic cholestasis were 79 and extra-trahepatic cholestasis were 42. Significant differences in characteristic of nutritional status with intrahepatic and extra-hepatic cholestasis were found (p=0,015), but there isn’t significant differences in age, birth weight, gestational age were observed. On examination of stool color, there was a significant difference (p<0,001), as well as laboratory results of SGOT, SGPT (p<0,05) between intra and extra-hepatic cholestasis. Meanwhile there isn’t significant differences in GGT, total bilirubin, direct bilirubin, indirect bilirubin, and ALP.Conclusions: There were differences in the characteristics of nutritional status, differences in laboratory results of SGOT, SGPT, and fecal clinics between intrahepatic and extrahepatic cholestasis.